Organic–inorganic hybrid materials doped with lithium ions - Żelazowska, Elżbieta; Borczuch-Łączka, Maria; Rysiakiewicz-Pasek, Ewa (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Organic–inorganic hybrid materials have been synthesized by the sol–gel method, using tetraethyl orthosilicate TEOS), poly(ethylene oxide) (PEO), net-polyacrylic-inter-net-polysiloxane, butyl acrylate, ethyl acetoacetate, tetrahydrofuran, acetonitrile and LiClO4 precursors and additives. Mass fractions of the organic additions in the gels were of ca 35–40 mass%. The hybrid materials obtained were amorphous, colourless, transparent or translucent, with room temperature ionic conductivities in a range of 10–4–10–3 Ω–1cm–1. The results of scanning electron microscopy equipped with energy dispersive X-ray spectroscopy (SEM/EDX), Fourier transform infrared spectroscopy and 29Si MAS Nuclear Magnetic Resonance analysis have revealed [SiO4] tetrahedrons polycondensation strongly influenced by organic precursors and chemical bonding between organic and inorganic parts of the gels obtained.
Optica Applicata, Vol. 38, 2008, nr 1, s. 137-146
Keywords: optyka; sol-gel; organic–inorganic hybrids; lithium-ion conductivity